Effects of albendazole treatment on neurocysticercosis: a randomised controlled trial. Issue 9 (21st May 2008) - Carpio, A; Kelvin, E A; Bagiella, E; Leslie, D; Leon, P; Andrews, H; Hauser, W A; ,
Abstract : Aim: The aim of this trial was to evaluate the effects of albendazole (ALB) on cyst disappearance, reduction of the number of cysts and seizure recurrence. Methods: 178 patients with new onset symptoms due to active or transitional neurocysticercosis were randomly assigned to receive either 800 mg of ALB daily or placebo for 8 days. All patients also received prednisone. Imaging studies were done at baseline and at months 1, 6 and 12 of follow-up. Results: Active cysts were identified in 59 of 88 people randomised to ALB and 57 of the 90 in the placebo arm. By 1 month, 31% were free of active cysts in the treatment group compared with 7% in the placebo group (p = 0.001). In addition, the ALB group had a greater reduction in the number of active cysts compared with the placebo group (p = 0.001). After 1 month following treatment there was no additional gain by treatment group in the disappearance or reduction in the number of active cysts. ALB treatment had little effect on cysts in the transitional or calcification stage. We found no difference between the ALB and placebo groups in symptoms during treatment or in seizure recurrence during the 12 months after treatment. Conclusion: Albendazole plus symptomatic treatment leads to the disappearance of active cysts in 31% of patients compared with 7% of those with symptomatic treatment alone. This treatment effect occurs within the first 30 days after treatment. Trial registration number: NCT00283699.